Hospitalizations and associated costs in a population‐based study of children with down syndrome born in Florida. Issue 11 (13th August 2014) - Dawson, April L.; Cassell, Cynthia H.; Oster, Matthew E.; Olney, Richard S.; Tanner, Jean Paul; Kirby, Russell S.; Correia, Jane; Grosse, Scott D.; Kirby, Russell; Browne, Marilyn
<x xml:space="preserve">Abstract</x> Background Our objective was to examine differences in hospital resource usage for children with Down syndrome by age and the presence of other birth defects, particularly severe and nonsevere congenital heart defects (CHDs). Methods This was a retrospective, population‐based, statewide study of children with Down syndrome born 1998 to 2007, identified by the Florida Birth Defects Registry (FBDR) and linked to hospital discharge records for 1 to 10 years after birth. To evaluate hospital resource usage, descriptive statistics on number of hospitalized days and hospital costs were calculated. Results were stratified by isolated Down syndrome (no other coded major birth defect); presence of severe and nonsevere CHDs; and presence of major FBDR‐eligible birth defects without CHDs. Results For 2552 children with Down syndrome, there were 6856 inpatient admissions, of which 68.9% occurred during the first year of life (infancy). Of the 2552 children, 31.7% (n = 808) had isolated Down syndrome, 24.0% (n = 612) had severe CHDs, 36.3% (n = 927) had nonsevere CHDs, and 8.0% (n = 205) had a major FBDR‐eligible birth defect in the absence of CHD. Infants in all three nonisolated DS groups had significantly higher hospital costs compared with those with isolated Down syndrome. From infancy through age 4, children with severe CHDs had the highest inpatient costs compared with children in the other sub‐groups. Conclusion Results support findings that for children with Down syndrome the presence of other anomalies influences hospital use and costs, and children with severe CHDs have greater hospital resource usage than children with other CHDs or major birth defects without CHDs. Birth Defects Research (Part A) 100:826–836, 2014. © 2014 Wiley Periodicals, Inc.